2021
DOI: 10.1007/s00259-021-05266-7
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent tumor detection for early and late FAPI-46 PET acquisition

Abstract: Introduction Positron emission tomography (PET) using small ligands of the fibroblast activation protein (FAP) was recently introduced. However, optimal uptake time has not been defined yet. Here, we systematically compare early (~ 10 min p.i.) and late (~ 60 min p.i.) FAPI-46 imaging in patients with various types of cancer. Methods This is a retrospective single-institutional study. Imaging was performed at the Essen University Hospital, Germany. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 16 publications
2
51
1
Order By: Relevance
“…had an equivalent lesion detection rate compared with a late time point (60 min p.i.) in a previous study 20 .…”
Section: Targeting Fap For Tumor Imagingmentioning
confidence: 60%
“…had an equivalent lesion detection rate compared with a late time point (60 min p.i.) in a previous study 20 .…”
Section: Targeting Fap For Tumor Imagingmentioning
confidence: 60%
“…Higher tumor-to-organ/blood ratios achieved with FAPI21 and FAPI46, as reported by Loktev et al (3), were promising; however, due to increased uptake of FAPI21 in the oral mucosa, thyroid, and salivary glands, FAPI46 was presumed more favorable. Accordingly, clinical imaging studies with 68 Ga-FAPI46 in a cohort of 69 patients by Ferdinandus et al (22) and six patients by Koerber et al (20) have demonstrated encouraging results. Another novel FAP inhibitor with a different structure based on the squaric acid motif, DOTA.SA.FAPi has also been introduced (23).…”
Section: Radiopharmaceuticals and Dosimetrymentioning
confidence: 94%
“…Accordingly, clinical imaging studies with 68 Ga-FAPI46 in a cohort of 69 patients by Ferdinandus et al. ( 22 ) and six patients by Koerber et al. ( 20 ) have demonstrated encouraging results.…”
Section: Radiopharmaceuticals and Dosimetrymentioning
confidence: 96%
“…One study was designed as a phase I investigation [24]. In 12/23 studies [ 68 Ga]Ga-FAPI was offered as a compassionate drug according to the German Medicinal Product Act § 13(2b) [25,26,35,36,[27][28][29][30][31][32][33][34]. In the remaining 10/23 papers, the trial phase was not speci ed or designated as "not applicable" [37][38][39][40][41][42][43][44][45][46].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The ndings of this preliminary study suggested a two-compartmental model assess [ 68 Ga]Ga-FAPI kinetics. Ferdinandus et al[32] compared early (~ 10 min p.i.) and late (~ 60 min p.i.)…”
mentioning
confidence: 99%